Novel Key Storage and Management Solution for the Security of Wireless Sensor Networks - Ali Hassan Sodhro; Ye Li; Madad Ali Shah (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As wireless sensor networks continue to grow in usage for distinct applications. Storage (memory) requirement and security are major problems for these resource limited networks. This paper present a novel and an efficient key establishment and management scheme for WSNs, named Random Initial and Master Key (RIMK).We showed that our proposed technique, manages keys randomly with less storage (i.e. only two keys), less communication and computation overhead compared to existing Localized Encryption and Authentication Protocol (LEAP), in which every node uses four different  keys in a static pattern and occupy greater storage space, which increases overhead and complexity in the network. Simulation results show that RIMK is more efficient and robust than LEAP. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2703